Developing a Framework of an Innovative Supply Chain in Thai Manufacturing Firms: An Interaction of Social Capital Theory and Knowledge-Based View - Boonsri Suteerachai; Akarapitta Meechaiwong; Pornkul Suksod; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The prime objective of the currents study is to explore and describe an innovative supply chain for the Thai manufacturing firms. The study has examined the direct impact of SC partner innovation, product innovation strategy, organizational innovation climate (OIC) and strategic relationship on the partner innovation performance. In addition to that the mediating role of product innovation strategy in the relationship between SC partner innovation and partner innovation performance is examined. Finally, the study has examined the moderating roe of organizational innovation climate and strategic relationship. The knowledge-based view and the social capital theory are used to develop the conceptual model. This idea has been extended in this research by analyzing the way in which it happens. For instance, it has been argued that there is a need for a suitable internal environment for innovation that can improve the chain of innovation linking innovativeness of partners in the supply chain with innovation strategy of the focal firm. In the next step, the right external climate can be set by establishing a strategic relation with partners in the supply chain to get innovative ideas. Lack of a cooperative environment cannot result in effective knowledge sharing with the partners in the network. This research study is unique in the sense that it complements the innovation chain with climate chain. Additions are made to the current knowledge by this study through the extension of the fact that value chains and SC for understanding the process of innovation chains. It is revealed through PIS that there is a positive influence on the performance of product innovation. There is a need to blend the internal climate for innovation and the external efforts with important suppliers to tap innovative ideas.